Reasoning in classroom dilemma situations: how pre-service teachers judge performance assessment - Greiner, Ulrike; Katstaller, Michaela; Oitner, Theresa (Frontiers in Education, 2024)
11 This study examines pre-service teachers’ reasoning structures based on their beliefs in the context of 12 school performance assessment. We used reflective writing to investigate pre-service teachers’ 13 judgement and reasoning regarding different functions of performance assessment. Forty-five 14 undergraduate pre-service teachers participated in our study. Using a mixed-method approach, we 15 conducted categorial and reconstructive text analyses as well as exploratory statistical analyses to 16 describe the participants’ reasoning structures. Such cognitive structures comprise potential solutions 17 to the performance assessment dilemmas that teachers face in their everyday teaching practice. We 18 found varying distributions of and relationships between (individual-, objective-, social-, and ability- 19 related) reference norms, (neutral, student-, and teacher-centered) reference perspectives as well as 20 (causal-analytic, normative, descriptive, and effect-oriented) modes of argumentation. Our 21 discussions related to future research activities on teachers’ reasoning structures in the classroom.